232k views
5 votes
How do I go about solving this?

How do I go about solving this?-example-1
User Fanda
by
5.5k points

2 Answers

7 votes

For this case we have the following functions:


f (x) = \frac {x} {2} -3\\g (x) = 3x ^ 2 + x-6

We must find
(f + g) (x). By definition, we have to:


(f + g) (x) = f (x) + g (x)

So:


(f + g) (x) = \frac {x} {2} -3+ (3x ^ 2 + x-6)\\(f + g) (x) = \frac {x} {2} -3 + 3x ^ 2 + x-6\\(f + g) (x) = + 3x ^ 2 + x + \frac {x} {2} -3-6\\(f + g) (x) = + 3x ^ 2 + \frac {2x + x} {2} -9\\(f + g) (x) = + 3x ^ 2 + \frac {3x} {2} -9

Answer:

Option B

User Jymdman
by
6.3k points
1 vote

Answer:

Option B is correct.

Explanation:

we are given
f(x) = (x)/(2)-3

and
g(x) = 3x^2+x-6

We need to find (f+g)(x)

We just need to add f(x) and g(x)

(f+g)x = f(x) + g(x)


(f+g)(x)=((x)/(2)-3)+(3x^2+x-6)\\(f+g)(x)=(x)/(2)-3+3x^2+x-6\\(f+g)(x)=3x^2+(x)/(2)+x-3-6\\(f+g)(x)=3x^2+(3x)/(2)-9\\

So, Option B is correct.

User Abris
by
5.8k points